Heterogeneity of the bone marrow niche. Issue 4 (July 2016) - Yu, Vionnie W.C.; Scadden, David T.
Abstract : Purpose of review: The bone marrow niche is increasingly recognized as heterogeneous with specific subtypes of mesenchymal niche cells governing the development or homeostasis of selective parenchymal hematopoietic subsets. The present review outlines recent efforts in dissecting these microniches regulated by unique cell pairings within the bone marrow and provides an overview of how the bone marrow orchestrates multiple facets of hematopoiesis. Recent findings: Recent advancement in technologies has significantly improved our understanding of the cellular and molecular constituents that contribute to regulation of hematopoiesis and to maintenance of the hematopoietic stem cells (HSCs). Transgenic mouse models that enable endogenous cell deletion or lineage tracing, coupled with advanced intravital microscopy has identified several mesenchymal cell types, including the osteolineage cells, megakaryocytes, macrophages, perivascular cells, and Schwann cells, to be indispensible regulators of hematopoiesis. These niche cells, when perturbed, each caused very specific hematopoietic consequences including impairment in B-cell maturation, T lineage development, erythropoiesis, and impact different aspects of HSC behavior such as quiescence, mobilization, and response to acute stress signals. Summary: The emerging concept is that the bone marrow environment is composed of multiple microniches, each consisting of unique pairing of distinct supportive stromal cells with distinct hematopoietic subtypes to regulate a particular branch of hematopoietic cell process. The bone marrow can be viewed as a carrier with subcompartments tailored to support different hematopoietic activities.